Natural selection on cork oak: allele frequency reveals divergent selection in cork oak populations along a temperature cline - Ramírez-Valiente, J. a; Lorenzo, Z.; Soto, A.; Valladares, F.; Gil, L.; Aranda, I. (Evolutionary Ecology, 2010)
A recent study of population divergence at neutral markers and adaptive traits in cork oak has observed an association between genetic distances at locus QpZAG46 and genetic distances for leaf size and growth. In that study it was proposed that certain loci could be linked to genes encoding for adaptive traits in cork oak and, thus, could be used in adaptation studies. In order to investigate this hypothesis, here we (1) looked for associations between molecular markers and a set of adaptive traits in cork oak, and (2) explored the effects of the climate on among-population patterns in adaptive traits and molecular markers. For this purpose, we chose 9-year-old plants originating from thirteen populations spanning a broad range of climatic conditions. Plants established in a common garden site were genotyped at six nuclear microsatellites and phenotypically characterized for six functional traits potentially related to plant performance. Our results supported the proposed linkage between locus QpZAG46 and genes encoding for leaf size and growth. Temperature caused adaptive population divergence in leaf size and growth, which was expressed as differences in the frequencies of the alleles at locus QpZAG46.
Keywords: Adaptation; Additive effects; Dominance; Natural selection; Overdominance; Quercus suber

Diversity and structure of ant communities associated with oak, pine, eucalyptus and arable habitats in Portugal - Cammell, M. E.; Way, M. J.; Paiva, M. R. (Insectes Sociaux, 1996)
In central Portugal, 28 species of ants were found in oak, 25 in pine, 35 in eucalyptus and 12 in arable habitats, a total of 43 species. They include five numerically dominant species, the exotic Argentine ant. Linepithema (Iridomyrmex) humile and four native species, Crematogaster scutel- laris, Pheidole pallidula, Tapinoma nigerrimum and Tetramorium hispanicum. L. humile occurred in 34 % of sampled sites. When present, it was abundant in all three arboreal habitats, where it was associated with strikingly decreased ant species richness and equitability. Such diversity was greater in L. humile - colonised arable habitats, where the ant was much less abundant than in the arboreal habitats. Where L. humile was absent, C. scutellaris and P pallidula were usually co-dominants in oak and pine, and T. nigerrimum and T. hispanicum in the arable habitat, but all were absent or rare in eucalyptus. Ants were numerically least abundant in eucalyptus but, in the absence of L. humile, species richness was greater and the community more equitable than in the other habitats. L. humile - absent arable habitats supported the poorest and least equitable ant community.
Keywords: Ants; community ecology; diversity; Dominance; Linepithema humile; Portugal.

Diversity and structure of ant communities associated with oak, pine, eucalyptus and arable habitats in Portugal - Cammell, M E; Way, M J; Paiva, M R (Insectes Sociaux, 1996)
In central Portugal, 28 species of ants were found in oak, 25 in pine, 35 in eucalyptus and 12 in arable habitats, a total of 43 species. They include five numerically dominant species, the exotic Argentine ant. Linepithema (Iridomyrmex) humile and four native species, Crematogaster scutel- laris, Pheidole pallidula, Tapinoma nigerrimum and Tetramorium hispanicum. L. humile occurred in 34 % of sampled sites. When present, it was abundant in all three arboreal habitats, where it was associated with strikingly decreased ant species richness and equitability. Such diversity was greater in L. humile - colonised arable habitats, where the ant was much less abundant than in the arboreal habitats. Where L. humile was absent, C. scutellaris and P pallidula were usually co-dominants in oak and pine, and T. nigerrimum and T. hispanicum in the arable habitat, but all were absent or rare in eucalyptus. Ants were numerically least abundant in eucalyptus but, in the absence of L. humile, species richness was greater and the community more equitable than in the other habitats. L. humile - absent arable habitats supported the poorest and least equitable ant community.
Keywords: Ants; community ecology; diversity; Dominance; Linepithema humile; Portugal.

Estructura básica generada por el arbolado en pastos semiáridos (ecosistemas de dehesa) - Rico, M; Puerto, A (Pastos, 1988)
A study was made of the effect on spatial distribution of species from semiarid grasslands. The basic structural aspects considered were: num- ber of species, exclusive species, and dominant species. Comparisons were made among the sites: under crown, canopy edge, and open grassland; in all three cases the N-S orientation was taken into account. The reduced number of species below the crown contrasts with the much higher number found at the canopy edge. However, in the latter case there were almost no exclusive or dominant species present since, owing to its intermedíate position, the most contrasted ecological charac- teristics correspond to the location receiving the most direct influence of the tree canopy and to the open spaces. Additionally, the similarity between the locations under the crown and the N exposure of the edge, and between the open spaces and S exposure of the edge leads to different results, according to whether orientation is considered or not
Keywords: Canopy effect; Dominance; exclusivity; floristic richness